Permasalahan Perumahan Mewujudkan Pembangunan Berkelanjutan di Indonesia - Jarwa Prasetya Sih Handoko; Arif Kusumawanto; Atyanto Dharoko; Eugenius Pradipto (Universitas Sebelas Maret Surakarta, 2022)
The research has a background of various housing development problems that require solutions, because housing is a basic human need. Development should be able to realize decent and sustainable housing, especially in developing countries including Indonesia. This research uses descriptive qualitative method with literature study or content analysis. The results of the study conclude that the problems of housing procurement include the high level of energy consumption of residential buildings, the low level of comfort of residential buildings, low levels of building health, building level considerations that are often ignored. security and also the level of respect for human dignity in the provision of housing need to be considered.